Vania Barraza and Carl Fischer, editors. Chilean Cinema in the Twenty-First-Century World. Wayne State UP, 2020. - Paul Ardoin (Studies in 20th & 21st Century Literature, 2023)
Review of Vania Barraza and Carl Fischer, editors. Chilean Cinema in the Twenty-First-Century World. Wayne State UP, 2020. 376 pp.
Keywords: Chilean cinema; transnational; film festivals; documentary; horror; trans*